Among Different Media: Gerhard Richter’s Landscape and its Medial Exchanges - Spathoni, Anthi-Danaé (Intermédialités / Intermediality, 2022)
From the artist’s very first photo-paintings to the most recent abstracts, landscape has been an omnipresent subject in Gerhard Richter’s career that presents a complete openness to different media, especially photography. This article attempts to study these multidisciplinary and intermedial references, the dialogue and mingling of the arts, as well as their contribution to landscape painting. Its purpose is to show not only how Richter integrates other works and characteristics from different arts, but also how works of art earlier in time can be perceived in his landscape depictions. To this end, the study of some representative examples helps us embrace various aspects of Richter’s practice, especially the ones that engage in a particular dialogue with abstraction, rendering the works of art, as it will be shown, into intra-, inter-, trans-, and multi-medial landscapes.